Correlation with serum Lactate dehydrogenase level and Hematological parameters before and after induction of remission in childhood Acute lymphoblastic leukemia- A prospective study (TAJ: Journal of Teachers Association, 2023)
The relationship between serum LDH (lactate dehydrogenase) and the course of neoplasia had been well established in different studies. It might be a promising tool as assessing serum is easy, readily available and cheap in the  prognosis of childhood Acute Lymphoblastic Leukemia (ALL). This study is aimed to evaluate the role of serum LDH before and after induction of remission in childhood ALL. This study was conducted at the Department of Pediatrics, Rajshahi Medical College Hospital, and Rajshahi for a period of two years. Total 30 children aged from 1-12 years newly diagnosed cases of ALL were included. Each patient underwent clinical evaluation and relevant investigations. All information was recorded in a separate case record form. Collected data were analyzed using the statistical software SPSS 23. Mean age of the studied children was 5.03±3.17 years. Male children were 66.7% and female children were 33.3%. Mean value of serum LDH was significantly lower at 29th days of induction of remission compared to the value before chemotherapy (432.40±310.52 U/L vs. 829.10±345.58 U/L, p +0.75, p